2018
DOI: 10.1007/s00737-018-0904-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of depression among HIV-positive perinatal women receiving antiretroviral therapy in India

Abstract: To assess the prevalence and correlates of perinatal depression, 200 HIV-positive pregnant/post-partum women receiving antiretroviral therapy (ART) were interviewed at eight government ART centers in four states across India. 52.5% (105) participants had depressive symptomology (Edinburgh Postnatal Depression Scale score > 13) while 23% of the participants reported thoughts of self-harm; there was no difference between pregnant and postpartum participants. Poor illness perception was associated with depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
5
3
Order By: Relevance
“…However, the current study prevalence falls within the range of prior prevalence estimates reported in sub-Saharan Africa and South Africa (42.2-49.3%), such as a prevalence of depressive symptoms of 43% reported by Kakyo et al [45] in a rural district in Uganda. The prevalence is also lower than the 52.5% reported from a study conducted in India among women on ART [46].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…However, the current study prevalence falls within the range of prior prevalence estimates reported in sub-Saharan Africa and South Africa (42.2-49.3%), such as a prevalence of depressive symptoms of 43% reported by Kakyo et al [45] in a rural district in Uganda. The prevalence is also lower than the 52.5% reported from a study conducted in India among women on ART [46].…”
Section: Discussioncontrasting
confidence: 66%
“…Furthermore, there was no association between non-disclosure of HIV positive status and the development of PND, even though a quarter of the mothers who reported PND symptoms had not disclosed their status to any family member and did not know their partner’s HIV status. Sarna et al [ 46 ] suggest that non-disclosure of HIV status to family members due to stigma and concerns about having a HIV negative child may predispose women to PND.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of perinatal depression is higher than 38.4% in a similar study in Ethiopia 21 . The prevalence of antenatal depression of 61.6% as measured by the EPDS with a cutoff ≥13 is slightly higher than the prevalence found in a previous study in Ekiti State, Nigeria (49.5%) 28 , 47.6% in Addis Ababa, Ethiopia 21 , and 52.5% in India among women on ART 29 . The differences in prevalence might be due to differences in sociodemographic characteristics and tools used to assess depression.…”
Section: Discussioncontrasting
confidence: 58%
“…It is estimated that more than 60% and 40% of people living with HIV in China exhibited symptoms of depression and anxiety respectively . Moreover, depression and anxiety have been linked to suboptimal HIV treatment outcomes, worse quality of life and increased mortality .…”
Section: Introductionmentioning
confidence: 99%